Geometry Mosaic to Improve Spatial-Visual Intelligence of Children Age 5-6 Years - Qurniyawati, Qurniyawati; Tasu'ah, Neneng (BELIA: Early Childhood Education Papers, 2020)
This study aims to determine whether the application of a geometric mosaic can improve the spatial-visual intelligence of children aged 5-6 years. This research was conducted at Mutiara Hati kindergarten in Manyaran, Semarang by using a pre-experimental design method in the form of One Group Pretest-Posttest. The populations in this study were 45 children of class B in Mutiara Hati kindergarten in Manyaran, Semarang. The sampling technique in this study is purposive sampling, where the criteria for determining the sample are children who do not understand the criteria for spatial-visual ability. The sample used in this study was 30 children. The data from the pretest and posttest were processed using the SPSS application. The researcher also collected documentation that served as supporting data. The data results were obtained through statistical calculations through paired sample t-test. The results of the calculation of the hypothesis can be accepted then the value of tcount must be smaller than ttable (tcount <ttabel) and Sig. <0.05. The results show that the value of tcount <ttabel is -7,350 <1,697 and Sig. 0,000 <0.05 so that Ha can be accepted. Based on this description, it can be concluded that the geometric mosaic can improve the spatial-visual intelligence of children aged 5-6 years at Mutiara Hati kindergarten in Manyaran, Semarang.